The Role of School Adaptation and Self-Concept in Influencing Chinese High School Students’ Growth in Math Achievement - Zhang, Danhui; Cui, Yiran; Zhou, Yuan; Cai, Mengfei; Liu, Hongyun (Frontiers in Psychology, 2018)
A longitudinal designed research was conducted to provide empirical evidence regarding with the influences of three dimension of students’ adaptation school adaptation, including learning adaptation, stress management, and personal communication, on their math achievement growth over the first year in high school. Student math achievement growth was measured using the student growth percentile (SGP) score. Structural equation modeling was used to test for the possible mediating role of self-concept behind those three relationships. Based on the model comparison, it was discovered that school adaptation significantly and positively influence student math achievement growth via mediating student academic self-concept, rather than showing direct impacts on students. The findings of this study have important implications for educators and parents to help students in education practice.